Dal dono al souvenir. Pratiche del dare e avere tra economia del turismo e cultura dell’ospitalità - Lucilla Rami Ceci (EtnoAntropologia)
The Tourist economy is now the most obvious tip of the complex structure of the post –colonial societies. The tourist economy substituted in many countries defined as emerging, gradually and not without destabilizing effect on social and political relations, the traditional economy with western models of development. In these societies the tourism has become essential for the presence of an attractive cultural heritage – often valued only for the archaeological endowment – and the lack  of other industrial activities. Here, just a long time, sites of historical and natural interest make up the scene of contacts between locals and visitors.